Reduced exercise capacity in pediatric post-COVID syndrome correlates with time post infection and does not affect quality of life - Stein, Lothar; Mackenrodt, Svea; Kück, Momme; Haufe, Sven; Kerling, Arno; Tegtbur, Uwe; Skerries, Valentina; Wetzke, Martin; Happle, Christine (Frontiers in Pediatrics, 2025)
ObjectivesPost-COVID syndrome (PCS) in children and adolescents is reported less frequently and typically of shorter duration than in adults but can be associated with significant morbidity and reduction of quality of life (QoL). In pediatric PCS, data on exercise capacity (EC) are rare.MethodsThis prospective, monocentric, cross-sectional study, analyzed EC, QoL, and clinical parameters in pediatric patients with PCS (n = 29/53 girls, 14.4 ± 2.5 years). A total of 210.0 ± 104.2 days passed between SARS-CoV-2 infection and study-related examinations.ResultsThe main PCS symptoms were reduced subjective EC (92.4%), shortness of breath (64.2%), concentration difficulties (60.4%), and breathlessness (47.2%). In patients with PCS, EC was 76.6 ± 16.0% VO2peakpredicted and maximum workload 76.0 ± 17.9% norm. Overall QoL (Kindl-R total score) was 89.2 ± 17.3% norm, self-assessed physical wellbeing was 60.7 ± 30.4% norm, and emotional wellbeing was 85.1 ± 23.2% norm. We grouped the PCS patients into deconditioned vs. conditioned (threshold 80% of VO2peakpredicted EC). No group differences in age, bodyweight, height, muscle mass, fat percentage, BMI, lung function, neuropsychological symptoms, and wellbeing were found. While maximum workloads and VO2peak differed significantly according to grouping, lactate levels and self-assessed exertion were comparable. However, elapsed time after SARS-COV-2 infection was significantly shorter in deconditioned vs. conditioned patients (mean 198.5 ± 120.7 vs. 230.8 ± 62.6 days; p = 0.021).ConclusionPediatric PCS is associated with reduced EC, which is significantly impacted by time post SARS-CoV-2 infection, but does not appear to affect the QoL or self-esteem of the patients in this study.